THE OCCUPATIONAL STANDARDS AS A TOOL OF THE HUMAN RESOURCE MANAGEMENT IN THE EDUCATIONAL ORGANIZATION - Vladimir I. Blinov; Ekaterina Yu. Esenina; Olga F. Klink; Elena A. Rykova; Alla A. Faktorovich (Высшее образование в России)
The article focuses on the professional standards features and benefits. These documents represent the current requirements for modern qualifications. The authors provide the main areas of the occupational standards in order to develop of the staff policy in the educational organization.